2001
DOI: 10.1046/j.1523-1747.2001.01352.x
|View full text |Cite
|
Sign up to set email alerts
|

αvβ6 Integrin Upregulates Matrix Metalloproteinase 9 and Promotes Migration of Normal Oral Keratinocytes

Abstract: The integrin alpha v beta 6 is a fibronectin receptor that is undetectable on normal keratinocytes in situ, but is increased significantly in wound healing and in culture-established keratinocytes, suggesting that it may promote changes associated with cell motility. Using normal human oral keratinocytes we have shown that cultured cells express relatively high levels of alpha v beta 6 and this integrin has a functional role in both cell adhesion and migration towards fibronectin. We provide experimental evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
71
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 40 publications
9
71
0
1
Order By: Relevance
“…Sequence 3 gave the most efficient knockdown and was used in subsequent experiments. VB6, BICR56 and CA1 express high levels of endogenous Eps8 and we have shown previously that these cells migrate well in vitro (Thomas et al, 2001;Ramsay et al, 2007). Although inhibition of Eps8 expression had no effect on cell growth in any of the cell lines (data not shown), migration of VB6, BICR56 and CA1 cells towards fibronectin was significantly suppressed (VB6, Po0.02; BICR56 Po0.02; CA1 Po0.0003; Figure 3b).…”
Section: Inhibition Of Eps8 Expression Suppresses Cell Migration and supporting
confidence: 50%
See 3 more Smart Citations
“…Sequence 3 gave the most efficient knockdown and was used in subsequent experiments. VB6, BICR56 and CA1 express high levels of endogenous Eps8 and we have shown previously that these cells migrate well in vitro (Thomas et al, 2001;Ramsay et al, 2007). Although inhibition of Eps8 expression had no effect on cell growth in any of the cell lines (data not shown), migration of VB6, BICR56 and CA1 cells towards fibronectin was significantly suppressed (VB6, Po0.02; BICR56 Po0.02; CA1 Po0.0003; Figure 3b).…”
Section: Inhibition Of Eps8 Expression Suppresses Cell Migration and supporting
confidence: 50%
“…We have shown previously that around 80-90% of OSCC express high levels of avb6, and that it promotes tumor cell migration and invasion (Thomas et al, 2001;Nystrom et al, 2006). Furthermore, we have shown recently that avb6-dependent invasion of VB6 Figure 5 Eps8 modulates integrin-dependent Rac1 activation and migration.…”
Section: Eps8 Upregulation Promotes Cell Migration and Invasion Lf Yamentioning
confidence: 91%
See 2 more Smart Citations
“…The avb6 heterodimer has been shown to modulate several processes in keratinocytes, including migration on fibronectin and vitronectin, and also fibronectin-dependent upregulation of matrix metalloproteinase-9 (MMP-9) (Huang et al, 1998;Thomas et al, 2001a). In addition to promoting cell migration and MMP-9 upregulation, we have demonstrated that increased expression of avb6 in squamous cell carcinoma cell lines produces a more invasive phenotype; such increased aggressive behaviour is avb6-dependent and is modulated through altered protease expression (Thomas et al, 2001b,c).…”
mentioning
confidence: 99%